Feasibility of using tissue autolysis to estimate the postmortem interval in horses. (September 2021) - Wenzlow, Nanny; Neal, Dan; Stern, Adam W.; Prakoso, Dhani; Liu, Junjie J.; Delcambre, Gretchen H.; Beachboard, Sally; Long, Maureen T.
Estimation of the postmortem interval (PMI) is a poorly studied field in veterinary pathology. The development of field-applicable methods is needed given that animal cruelty investigations are increasing continually. We evaluated various histologic criteria in equine brain, liver, and muscle tissue to aid the estimation of PMI in horses, which is central to forensic investigations of suspicious death. After death, autolysis proceeds predictably, depending on environmental conditions. Currently, no field-applied methods exist that accurately estimate the PMI using histology in animals or humans through quantification of autolysis. Brain, liver, and skeletal muscle from 12 freshly euthanized horses were held at 22°C and 8°C for 72 h. Tissues were sampled at T0h, T1h, T2h, T4h, T6h, T12h, T24h, T36h, T48h, T60h, and T72h. For each tissue, we quantified 5 to 7 criteria associated with autolysis, based on the percentage of microscopic field involved. Each criterion was modeled, with temperature and time as independent variables. Changes were most predictable in liver and muscle over the first 72 h postmortem. The criteria for autolysis that were present most extensively at both temperatures were hepatocyte individualization and the separation of bile duct epithelium from the basement membrane. The changes that were present next most extensively were disruption of myofiber continuity, hypereosinophilia, and loss of striation. Brain changes were highly variable. The high statistical correlation between the parameter "autolysis" and the variables "time/temperature", indicates that autolysis is progressive and predictable. Further investigation of these criteria is needed to establish histologic algorithms for PMI.